Effects of single‐agent bortezomib as post‐transplant consolidation therapy on multiple myeloma‐related bone disease: a randomized phase II study. (6th April 2017) - Sezer, Orhan; Beksac, Meral; Hajek, Roman; Sucak, Gülsan; Cagirgan, Seckin; Linkesch, Werner; Meltem Akay, Olga; Gülbas, Zafer; Nahi, Hareth; Plesner, Torben; Snowden, John A.; Timurağaoğlu, Ayşen; et al.
Summary: This phase II study explored the effects of bortezomib consolidation versus observation on myeloma‐related bone disease in patients who had a partial response or better after frontline high‐dose therapy and autologous stem cell transplantation. Patients were randomized to receive four 35‐day cycles of bortezomib 1·6 mg/m 2 intravenously on days 1, 8, 15 and 22, or an equivalent observation period, and followed up for disease status/survival. The modified intent‐to‐treat population included 104 patients (51 bortezomib, 53 observation). There were no meaningful differences in the primary endpoint of change from baseline to end of treatment in bone mineral density (BMD). End‐of‐treatment rates (bortezomib versus observation) of complete response/stringent complete response were 22% vs. 11% ( P = 0·19), very good partial response or better of 80% vs. 68% ( P = 0·17), and progressive disease of 8% vs. 23% ( P = 0·06); median progression‐free survival was 44·9 months vs. 21·8 months ( P = 0·22). Adverse events observed ≥15% more frequently with bortezomib versus observation were diarrhoea (37% vs. 0), peripheral sensory neuropathy (20% vs. 4%), nausea (18% vs. 0) and vomiting (16% vs. 0). Compared with observation, bortezomib appeared to have little impact on bone metabolism/health, but was associated with trends for improved myeloma response and survival.